Genome wide natural variation of H3K27me3 selectively marks genes predicted to be important for cell differentiation in Phaeodactylum tricornutum. Issue 6 (31st December 2020) - Zhao, Xue; Rastogi, Achal; Deton Cabanillas, Anne Flore; Ait Mohamed, Ouardia; Cantrel, Catherine; Lombard, Berangère; Murik, Omer; Genovesio, Auguste; Bowler, Chris; Bouyer, Daniel; Loew, Damarys; Lin, Xin; et al.
Summary: In multicellular organisms, Polycomb Repressive Complex2 (PRC2) is known to deposit tri‐methylation of lysine 27 of histone H3 (H3K27me3) to establish and maintain gene silencing, critical for developmentally regulated processes. The PRC2 complex is absent in both widely studied model yeasts, which initially suggested that PRC2 arose with the emergence of multicellularity. However, its discovery in several unicellular species including microalgae questions its role in unicellular eukaryotes. Here, we use Phaeodactylum tricornutum enhancer of zeste E ( z ) knockouts and show that P. tricornutum E ( z ) is responsible for di‐ and tri‐methylation of lysine 27 of histone H3. H3K27me3 depletion abolishes cell morphology in P. tricornutum providing evidence for its role in cell differentiation. Genome‐wide profiling of H3K27me3 in fusiform and triradiate cells further revealed genes that may specify cell identity. These results suggest a role for PRC2 and its associated mark in cell differentiation in unicellular species, and highlight their ancestral function in a broader evolutionary context than currently is appreciated.